2022
DOI: 10.1021/acs.chemmater.2c02660
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity in HfO2 from a Coordination Number Perspective

Abstract: Ferroelectricity observed in thin-film HfO 2 , either doped with Si, Al, and so forth or in the Hf 0.5 Zr 0.5 O 2 form, has gained great technical significance. While a trilinear coupling between phonon modes could explain its ferroelectric distortion, from a practical perspective, one may be concerned with a theory that is more straightforward to predict similar ferroelectric candidates through some apparent features of HfO 2 and ZrO 2 . In this work, we propose that the 7 cation coordination number of HfO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 72 publications
(94 reference statements)
0
16
0
Order By: Relevance
“…The possible reason for this is that Lu 3+ is smaller than Y 3+ , and Fanions may penetrate the z = 0 plane (made of Lu 3+ ) to prefer the external path. It is interesting to note that the preferred path of LuOF corresponds to the larger P S , which is quite unusual among Pca2 1 ferroelectrics [35]. Subsequently, we compare LuOF and YOF with HfO 2 in terms of their theoretical ferroelectric and electronic properties.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…The possible reason for this is that Lu 3+ is smaller than Y 3+ , and Fanions may penetrate the z = 0 plane (made of Lu 3+ ) to prefer the external path. It is interesting to note that the preferred path of LuOF corresponds to the larger P S , which is quite unusual among Pca2 1 ferroelectrics [35]. Subsequently, we compare LuOF and YOF with HfO 2 in terms of their theoretical ferroelectric and electronic properties.…”
Section: Resultsmentioning
confidence: 88%
“…On the other hand, table 2 lists the ten candidate materials that exhibit a finite polarization in their Pca2 1 phase. Among these, YOF has already been reported [35] but is included in our comparison due to its potentially excellent ferroelectric properties. Phonon instability is not observed in any of these ten compounds in their relaxed Pca2 1 phase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In situations where there is no mechanical strain, it would be even more difficult to induce symmetry breaking. In this case, a specific range of the relative ratio of the radii of cation and anion may be a key factor as Yuan et al recently suggested (Figure b). According to their computational simulation, the coordination number 7 of HfO 2 and ZrO 2 , arising from their characteristic ionic radii ratio value at the boundary between coordination numbers 6 and 8, is critical for the ferroelectricity with a rather strong crystallographic distortion with noncentrosymmetry …”
mentioning
confidence: 90%